Multifunctional roles of Saccharomyces cerevisiae Srs2 protein in replication, recombination and repair - Niu, Hengyao (FEMS Yeast Res, 2016)
The Saccharomyces cerevisiae Srs2 DNA helicase has important roles in DNA replication, recombination and repair. In replication, Srs2 aids in repair of gaps by repair synthesis by preventing gaps from being used to initiate recombination. This is considered to be an anti-recombination role. In recombination, Srs2 plays both prorecombination and anti-recombination roles to promote the synthesis-dependent strand annealing recombination pathway and to inhibit gaps from initiating homologous recombination. In repair, the Srs2 helicase actively promotes gap repair through an interaction with the Exo1 nuclease to enlarge a gap for repair and to prevent Rad51 protein from accumulating on single-stranded DNA. Finally, Srs2 helicase can unwind hairpin-forming repeat sequences to promote replication and prevent repeat instability. The Srs2 activities can be controlled by phosphorylation, SUMO modification and interaction with key partners at DNA damage or lesions sites, which include PCNA and Rad51. These interactions can also limit DNA polymerase function during recombinational repair independent of the Srs2 translocase or helicase activity, further highlighting the importance of the Srs2 protein in regulating recombination. Here we review the myriad roles of Srs2 that have been documented in genome maintenance and distinguish between the translocase, helicase and additional functions of the Srs2 protein.